THE RELATIONSHIP OF TEACHING CLARITY AND STUDENT ACADEMIC MOTIVATION IN ONLINE CLASSES: Received: 6th September 2022; Revised: 20th October 2022, 27th January 2023; Accepted: 28th January 2023 - Liang, Jiawei (PUPIL: International Journal of Teaching, Education and Learning, 2023)
Abstract Due to the outbreak of Covid-19, a large number of educational institutions had to temporarily discontinue their offline delivery models in favor of online courses. Teaching clarity has always been an important factor in teaching and learning, but due to the implementation of online courses, teaching clarity has been greatly impacted by various factors of new course delivery model. It is unknown how student academic motivation will be affected by teaching-clarity behaviors in this context. This study collected data from undergraduate students who adopted an online course delivery model to explore the relationship between teaching clarity and student academic motivation during covid-19. The regression result indicated that student motivation was significantly and positively related to teaching clarity in the online course delivery model, and that higher teaching clarity in online courses was associated with higher student motivation. The finding of this study shed light on the teaching-clarity behavior as a key to motivating students in the online course delivery model, with revelatory implications for teachers to design online courses and motivate students in the future.